2022
DOI: 10.3389/fphar.2022.903599
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone Induces Cell Cycle Arrest, Apoptosis and Autophagy in Colorectal Cancer Cells

Abstract: Colorectal cancer (CRC) is an aggressive cancer. Isoalantolactone (IATL) has been reported to exert cytotoxicity against various cancer cells, but not CRC. In this study, we explored the anti-CRC effects and mechanism of action of IATL in vitro and in vivo. Our results demonstrated that IATL inhibited proliferation by inducing G0/G1 phase cell cycle arrest, apoptosis and autophagy in CRC cells. Repression of autophagy with autophagy inhibitors chloroquine (CQ) and Bafilomycin A1 (Baf-A1) enhanced the anti-CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Hence, the WECP treatment promoted cell cycle progression ( Figures 2B, C ). The proteins, Cyclin A, CDK2, CDK4, and P21, regulate cell cycle progression from G0/G1 to S ( Li et al, 2022 ). We then quantified these cell cycle-related proteins by western blotting to verify the foregoing results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the WECP treatment promoted cell cycle progression ( Figures 2B, C ). The proteins, Cyclin A, CDK2, CDK4, and P21, regulate cell cycle progression from G0/G1 to S ( Li et al, 2022 ). We then quantified these cell cycle-related proteins by western blotting to verify the foregoing results.…”
Section: Resultsmentioning
confidence: 99%
“…The DPCs cycle was detected by propidium iodide (PI) staining and flow cytometry ( Li et al, 2022 ). Briefly, DPCs were seeded in six-well plates at a density of 1.5 × 10 5 /well and treated with various WECP concentrations for 24 h. The following day, the cells were harvested, washed with phosphate-buffered saline (PBS), and centrifuged (5425 R; Eppendorf, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Cellular proliferation was determined by clone formation and 5′-Ethynyl-2′-deoxyuridine (EdU) incorporation assays as described previously [ 34 ]. For the colony formation assay, 800 cells were plated in 6-well plates and then incubated with different concentrations of PPII (0.5, 1, and 2 μM) for 24 h. Thereafter, the cells were cultured with fresh medium for ~12 days before being stained with 0.3% crystal violet.…”
Section: Methodsmentioning
confidence: 99%
“…All mice were maintained in individual ventilated cages in an animal handling room at the Hong Kong Baptist University. A xenograft mouse model was established as described previously [ 34 ]. Briefly, each mouse was inoculated subcutaneously in the flank with the HCT116 cells (2 × 10 6 /mice).…”
Section: Methodsmentioning
confidence: 99%
“…Isoalantolactone (IAL) is a sesquiterpene lactone naturally found in the roots of Inula helenium L. with cytotoxicity against different cancer cells. Li et al (2022) observed that IAL induces G0/G1 phase cell cycle arrest, apoptosis, and autophagy in colorectal cancer (CRC) cell lines, including HCT116 and SW620. Pro-apoptotic activity of IAL in these cancer cell lines was shown by downregulation of anti-apoptotic proteins Bcl-2, Bcl-xL, and Mcl-1 as well as downregulation of pro-apoptotic protein Bax and activation of PARP enzyme in both cancer cell lines.…”
Section: Sesquiterpene Lactones With Pro-apoptotic Activities In Cancermentioning
confidence: 99%